Complete nucleotide sequence of a gene encoding a functional human class I histocompatibility antigen (HLA-CW3). - Sodoyer, R (1984)
The HLA-CW3 gene contained in a cosmid clone identified by transfection expression experiments has been completely sequenced. This provides, for the first time, data on the structure of HLA-C locus products and constitutes, together with that of the gene coding for HLA-A3, the first complete nucleotide sequences of genes coding for serologically defined class I HLA molecules. In contrast to the organisation of the two class I HLA pseudogenes whose sequences have previously been determined, the sequence of the HLA-CW3 gene reveals an additional cytoplasmic encoding domain, making the organisation of this gene very similar to that of known H-2 class I genes and also the HLA-A3 gene. The deduced amino acid sequences of HLA-CW3 and HLA-A3 now allow a systematic comparison of such sequences of HLA class I molecules from the three classical transplantation antigen loci A, B, C. The compared sequences include the previously determined partial amino acid sequences of HLA-B7, HLA-B40, HLA-A2 and HLA-A28. The comparisons confirm the extreme polymorphism of HLA classical class I molecules, and permit a study of the level of diversity and the location of sequence differences. The distribution of differences is not uniform, most of them being located in the first and second extracellular domains, the third extracellular domain is extremely conserved, and the cytoplasmic domain is also a variable region. Although it is difficult to determine locus-specific regions, we have identified several candidate positions which may be C locus-specific.